Analisis Citra Satelit Himawari-8 Terkait Kejadian Puting Beliung Di Kabupaten Bogor (Studi Kasus 02 November 2021) - Ade Febrian; Syaiful Amri (JFT : Jurnal Fisika dan Terapannya, 2023)
Puting Beliung is a strong-rotating wind originating from Cumulonimbus clouds with a speed of more than 34.8 knots or 64.4 km/hour that occurs short time. Puting Beliung occurred on November 2, 2021, at 2 pm in the Kampung Dukuh area, Pasirmukti Village, Citeureup District, Bogor Regency (106° 53' 47.99"E and 6° 31' 5.2"S). The research data are surface air observation data from Bogor Climatology Station, Himawari-8 satellite data, and Copernicus CDS reanalysis data. This study aims to analyze the dynamics of the atmosphere during the occurrence of wind phenomena in a tornado in the Kampung Dukuh area, Pasirmukti Village, Citeureup District, Bogor Regency. This study method is a descriptive analysis of Himawari-8 satellite imagery using SATAID software. The results of this study indicate that tornadoes occur due to shear lines and strong-atmospheric lability in the Bogor and surrounding areas, thus triggering the formation of local convective clouds characterized by cloud peak temperatures reaching -69oC.